2000
DOI: 10.1016/s0002-9440(10)64610-x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 17 Aneusomy Detected by Fluorescence in Situ Hybridization in Vulvar Squamous Cell Carcinomas and Synchronous Vulvar Skin

Abstract: Vulvar squamous cell carcinoma (SCC) affects a spectrum of women with granulomatous vulvar diseases, human papillomavirus (HPV) infections, and chronic inflammatory vulvar dermatoses. To determine whether there is evidence of chromosomal instability occurring in synchronous skin surrounding vulvar SCCs, we investigated abnormalities in chromosome 17 copy number. Samples of SCC, vulvar intraepithelial neoplasia (VIN), and surrounding vulvar skin were obtained from all vulvar excisions performed for squamous neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Structural and numerical aberrations targeting chromosome 17 are often reported in tumors from various tissues (Olaharski et al 2006), whereas the pattern that chromosome 13 is lost and chromosome 17 is stable, was common for the three cell lines in this study, indicating the possibility that the loss of chromosome 13 may play an important role in the chromosomal aberration of hMSCs to acquire growth advantages under the given culturing condition. Similar karyotypic changes were evident in cultured human embryonic stem cells, involving the gain of chromosome 17 or chromosome 12 (Carlson et al 2000;Draper et al 2004). It is thus conjectured that the aneuploidy developed through chromosomal loss from diploid cells arises through different mechanisms from tetraploid intermediate.…”
Section: Discussionmentioning
confidence: 71%
“…Structural and numerical aberrations targeting chromosome 17 are often reported in tumors from various tissues (Olaharski et al 2006), whereas the pattern that chromosome 13 is lost and chromosome 17 is stable, was common for the three cell lines in this study, indicating the possibility that the loss of chromosome 13 may play an important role in the chromosomal aberration of hMSCs to acquire growth advantages under the given culturing condition. Similar karyotypic changes were evident in cultured human embryonic stem cells, involving the gain of chromosome 17 or chromosome 12 (Carlson et al 2000;Draper et al 2004). It is thus conjectured that the aneuploidy developed through chromosomal loss from diploid cells arises through different mechanisms from tetraploid intermediate.…”
Section: Discussionmentioning
confidence: 71%
“…By using fluorescent in situ hybridization (FISH) Carlson et al (2000) enumerated chromosome 17 in 43 VIN III and VSCC specimens from 33 patients. They found that 76-100 % of the samples were aneuploid with regard to chromosome 17.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization results were examined and analyzed using a Zeiss Axioplan2 fluorescent microscope and Smartcapture 4.1 software. For analysis, we used the criteria found in Carlson et al (39): nuclei of 2-3 different areas were examined in each experiment, totalling 80-120 nuclei. Regions with a high background level or without at least one signal of each probe were not included.…”
Section: Methodsmentioning
confidence: 99%